2010
DOI: 10.1243/13506501jet685
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of tribological behaviour of dental composites and tooth enamel: An energy approach

Abstract: In this article, an energy approach based on the correlation between dissipated friction energy and wear volume was used to compare wear resistances of human tooth enamel and four composite dental materials: Arkon, Ecusit, Ful-Fil, and Filtek. The results of the study showed that the wear resistance of enamel is approximately one order or more higher than the one obtained for the dental materials. The effectiveness of the approach used has also been shown. Scanning electron microscopy (SEM) examinations and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…It was further concluded that incorporation of nanoalumina increased hardness and wear resistance of the composites. Sajewicz 13 compared the wear resistance of human tooth enamel and four different commercially available dental materials such as Arkon, Ecusit, Ful-Fil, and Filtek, and found that Filtek dental material exhibited better wear resistance as compared with other materials because it consisted of more amounts of nanofillers. Nowadays, most of the researches are focused on the material properties, physical characterizations, chemical composition, as well as the wear resistance of the dental composites.…”
Section: Introductionmentioning
confidence: 99%
“…It was further concluded that incorporation of nanoalumina increased hardness and wear resistance of the composites. Sajewicz 13 compared the wear resistance of human tooth enamel and four different commercially available dental materials such as Arkon, Ecusit, Ful-Fil, and Filtek, and found that Filtek dental material exhibited better wear resistance as compared with other materials because it consisted of more amounts of nanofillers. Nowadays, most of the researches are focused on the material properties, physical characterizations, chemical composition, as well as the wear resistance of the dental composites.…”
Section: Introductionmentioning
confidence: 99%
“…No animal or human studies were identified. The included studies are listed in the Table 1 [22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The number of publications increased through the years and 13 of 17 articles were published after 2010.…”
Section: Study Selectionmentioning
confidence: 99%
“…The number of publications increased through the years and 13 of 17 articles were published after 2010. In addition, 13 studies were published in journals that covered research into mechanical engineering or technology of nanosized and nanostructured materials, including advanced ceramic materials and reinforced plastics and polymer composites [25][26][27][28][29][30][31][32][33][35][36][37][38]; three studies were published in journals that focused on the application of biomaterials and tissue engineering in the medical sciences [24,34,39] and only one was published in a dentistry journal [22].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations